Extracellular nuclease from a thermophile, streptomyces thermonitrificans: production, purification and partial characterization of - double strand preferential - deoxyribonuclease activity - Patil, N. S.; Deshmukh, Satej S.; Shankar, V. (Process Biochemistry, 2005)
A thermophilic strain of Streptomyces themionitrificans produced high levels of extracellular nuclease (designated as nuclease Stn beta) when grown on nutrient broth glucose medium. Maximal nuclease activity (51 U ml(-1)) was obtained, in 40 h, when the culture was grown on modified NBG medium at 45 degreesC. The enzyme was purified to homogeneity with an overall recovery of 5.6% and a specific activity of 10,833. The relative molecular mass of the purified enzyme, determined by gel filtration, was 22.4 kDa and it showed an obligate requirement for Mn2+ for activity. The optimum pH and temperature of nuclease Stn beta were 8.0 and 45 degreesC, respectively. The enzyme was inhibited by Mg2+ CO2+, Cu2+, Zn2+ and Hg2+, inorganic phosphate, pyrophosphate, dithiothreitol, beta-mereaptoethanol, EDTA and NaCl. Nuclease Stn beta was stable to high concentrations of urea and organic solvents but susceptible to low concentrations of SDS and guanidine hydrochloride. Nuclease Stn beta is a multifunctional enzyme with substrate specificity in the order of dsDNA > ssDNA much greater than RNA. The end products of dsDNA hydrolysis were predominantly oligonucleotides (85-90%) and small amounts of 5' mononucleotides (10-15%) suggesting an endo mode of action. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Endonuclease; extracellular nuclease; production; Purification; Streptomyces thermonitrificans

Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol

Hydrothermal synthesis of MCM-41 using differently manufactured amorphous dioxosilicon sources - Gaydhankar, T. R.; Samuel, V.; Joshi, P. N. (Materials Letters, 2006)
The influence of differently manufactured amorphous dioxosilicon sources such as fumed silica (FS), spray dried precipitated silica (PSI) and flash dried precipitated silica (PS,) on the course of structural development and properties of hydrothermally prepared siliceous MCM-41 phases have been investigated. Powder XRD, N-2 adsorption/desorption and scanning electron microscopy techniques were used for sample characterization. On the basis of results obtained from time dependent study on the progressive development of MCM-41 mesophases, the reactivity trend of dioxosilicon sources observed was as: FS > PS1 > PS2. MCM-41 synthesized using least expensive PS2 having less surface area has exhibited thicker pore walls but poor orderness, while MCM-41 prepared from expensive FS having high surface area has thinner pore walls and was well ordered. The extent of contraction caused by calcination, magnitude of the wall thickness and structural stability were found to be dependent on manufacturing process of dioxosilicon sources. The noticeable morphological differences were also observed by variations in the type of dioxosilicon sources used in the hydrothermal synthesis MCM-41 materials. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Characterization; dioxosilicon sources; Hydrothermal synthesis; MCM-41; porosity; Structural stability

Synthesis and characterization of novel polybenzimidazoles bearing pendant phenoxyamine groups - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
A novel aromatic diacid, 3, 5-dicarboxyl-4'-amino diphenyl ether, containing pendant phenoxy amine group was synthesized. Homo- and co-polybenzimidazoles containing different content of pendant phenoxyamine groups were synthesized by condensation of 3,3'-diaminobenzidine with this acid and a mixture of this acid and isophthalic acid in different ratio in polyphosphoric acid. Copolybenzimidazoles with structural variations were also synthesized based on this acid and pyridine dicarboxylic acid, terephthalic acid, adipic acid, or sebacic acid. The polymers have good solubility in polar aprotic solvents and strong acids and they form tough flexible films by solution casting. The polymers were characterized by different instrumental techniques (FTIR, TGA, DSC, XRD, etc.) and for solvent solubility, mechanical properties, inherent viscosity, and proton conductivity. The inherent viscosities of the polymers vary in the range of 0.62-1.52 dL/g. They have high thermal stability up to 475506 degrees C (IDT) in nitrogen, high glass transition temperatures (T-g) ranging from 313 to 435 degrees C and good tensile strength ranging from 58 to 125 MPa. Proton conductivity of homo polymer is 3.72 x 10(-3) S/cm at 25 degrees C and 2.45 x 10(-2) S/cm at 200 degrees C (c) 2008 Wiley Periodicals, Inc.
Keywords: Characterization; copolybenzimidazoles; High performance polymers; high temperature materials; pendant phenoxyamine group; polybenzimidazoles; synthesis

Purification and characterization of putative alkaline [Ni-Fe] hydrogenase from unicellular marine green alga, tetraselmis kochinensis NCIM 1605 - Bhosale, Siddharth H.; Pant, A.; Khan, Mohammad Islam (Microbiological Research, 2009)
Hydrogenase enzyme from the unicellular marine green alga Tetraselmis kochinensis NCIM 1605 was purified 467 fold to homogeneity. The molecular weight was estimated to be similar to 89kDa by SDS-PAGE. This enzyme consists of two subunits with molecular masses of similar to 70 and similar to 19 kDa. The hydrogenase was found to contain 10 g atoms of Fe and 1 g of atom of Ni per mote of protein. The specific activity of hydrogen evolution was 50 mu mol H-2/mg/h of enzyme using reduced methyl viologen as an electron donor. This hydrogenase enzyme has pl value similar to 9.6 representing its alkaline nature. The absorption spectrum of the hydrogenase enzyme showed an absorption peak at 425 nm indicating that the enzyme had iron-sulfur clusters. The total of 16 cysteine residues were found per mote of enzyme under the denaturing condition and 20 cysteine residues in reduced denatured enzyme indicating that it has two disulfide bridges. (C) 2007 Published by Elsevier GmbH.
Keywords: Characterization; Chemical modification; Ni-Fe hydrogenase; Tetraselmis kochinensis; Unicellular green algae

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48

Nitrophenoxy groups containing polybenzimidazoles as polymer electrolytes for fuel cells: synthesis and characterization - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Applied Polymer Science, 2010)
Polybenzimidazoles containing different contents of pendant nitrophenoxy groups were prepared by condensation of 3,3'-diamino-benzidine with a mixture of 3,5-dicarboxyl-4'-nitro diphenyl ether and isophthalic acid (IPA) in different ratios in polyphosphoric acid. The polymers are soluble in polar aprotic solvents, they have inherent viscosities in the range of 0.75-1.10 dL g(-1) and they form tough and transparent films on solution casting. They have good thermal stability with initial decomposition temperature ranging from 380 to 416 degrees C in nitrogen, good tensile strength ranging from 56 to 65 MPa and reasonably good oxidative stability. Phosphoric acid uptake of these polymers is low compared with PBI and membranes doped with phosphoric acid exhibit good proton conductivity in the range of 6.6x 10(-3) to 1.9x 10(-2) S/cm at 25 degrees C and 1.2x 10(-2) to 4.9x 10(-2) S/cm at 175 degrees C, compared with 3.9x 10(-3) S/cm at 25 degrees C and 3.2x 10(-2) S/cm at 175 degrees C for PBI. These membranes are suitable for applications as polymer electrolyte for fuel cell and presumably for gas separation at high temperature. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 3282-3292, 2010
Keywords: Characterization; membranes; pendant nitrophenoxy group; polybenzimidazoles; proton conductivity; synthesis

Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit

Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts prepared with different precipitating agents - Tangale, Nilesh P.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Joshi, Praphulla N. (Applied Catalysis A-General, 2013)
Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts (molar Cu:Al = 1:1) prepared by reduction of mixed oxide precursors synthesized using different precipitating agents viz, potassium carbonate, tetraalkyl ammonium hydroxides (TAAOHs) and urea was investigated. In order to assess the efficacy of TAAOH further, the chain length of tetraalkyl ammonium cations was also varied and the resulted catalysts were evaluated for their catalytic performance. The catalysts were characterized by powder X-ray diffraction, low temperature nitrogen adsorption, temperature programmed desorption of ammonia and UV-visible diffuse reflectance spectroscopy. The dependence of the catalyst performance on the precipitating agent employed during its synthesis has been clearly demonstrated. The use of TAAOH as precipitating agent led to the formation of a catalyst with better catalytic activity than those prepared using potassium carbonate and urea. Further improvement in the catalytic performance was observed when TAAOH with longer alkyl chain ammonium cation was used. The optimum catalyst prepared by reduction of mixed oxide precursor synthesized using tetrapropyl ammonium hydroxide as precipitating agent, showed highest cyclohexanol conversion (81.5%) and cyclohexanone selectivity (79.6%) at 250 degrees C on account of higher Cu+/Cu-0 ratio, well dispersed copper, higher surface area and lower total acidity with higher contribution of sites with moderate strength. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Characterization; Cu/Al2O3; Cyclohexanol dehydrogenation; Precipitating agent; Tetraalkyl ammonium hydroxide

Facile biological approach for immobilization, physicochemical characterization and antibacterial activity of noble metals nanocomposites - Parveen, Asra; Ali, Tayyab; Wahid, Malik; Rao, Srinath (Materials Letters, 2015)
The use of biopolymer as template to regulate metallic nanoparticles is promising field in green nanotechnology. We have designed a facile biological way for rapid synthesis and immobilization of gold and silver nanoparticles on alginate films using leaf extract of Cassia auriculata. The prepared gold bio-nanocomposite (Au-BNC) and silver bio-nanocomposite (Ag-BNC) were characterized by UV-vis spectroscopy, Fourier transform infrared spectroscopy, Transmission electron microscopy and Thermal analysis. The bio-nanocomposites exhibited good antibacterial activity against both gram positive (Bacillus subtilis) and gram negative (Escherichia coli) bacteria. The metal nanoparticle embedded films have number of applications in catalysis, optical biosensors, electronic, biomedical devices and environmental remediation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Alginate; Antibacterial; Bio-nanocomposites; Cassia auriculata; Characterization; Nanoparticles

Green synthesis of silver nanoribbons from waste X-ray films using alkaline protease - Shankar, Shiv; Prasad, R. G. S. V.; Selvakannan, P. R.; Jaiswal, Lily; Laxman, Ryali Seeta (Materials Express, 2015)
This work illustrates a facile approach to synthesize silver nanoribbons from waste X-ray films using alkaline protease from Beauveria sp. MTCC 5184 (BAP). The green synthesized nanoribbons have been characterized by UV-Vis spectroscopy, TEM, and FTIR. The UV-visible spectra gave maximum absorbance at 400 nm. TEM micrograph showed well-dispersed silver nanoribbons with an average length of 200-400 nm. FTIR result demonstrated the respective bands of the silver nanoribbons and proteins. XRD data revealed crystalline nature of silver nanoribbons dominated with (111) facets. In vitro antibacterial activity in terms of minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) showed 8/16 mu g/mL (MIC/MBC) against Staphylococcus aureus ATCC 29213 and 4/8 mu g/mL (MIC/MBC) against Escherichia coli ATCC 25922. The green synthesized silver nanoribbons showed excellent biocompatibility up to 40 mu g/mL concentrations on mouse fibroblast cell line (L929).
Keywords: Alkaline Protease; Characterization; Cytotoxicity; Silver Nanoribbons; Waste X-ray Film

Antimicrobial synergy of silver-platinum nanohybrids with antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality, and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to the available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100 degrees C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of similar to 59 nm. AgNPs, PtNPs, and AgPtNHs showed a zeta potential of -14.46, -1.09, and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin, and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.
Keywords: antibiofilm; antimicrobial synergy; biogenic synthesis; Characterization; silver-platinum nanohybrids

Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites

Green adeptness in synthesis of non-toxic copper and cobalt oxide nanocomposites with multifaceted bioactivities - Mane, Pramod C.; Kadam, Deepali D.; Khadse, Ashok N.; Chaudhari, Aditya R.; Ughade, Supriya P.; Agawane, Sachin B.; Chaudhari, Ravindra D. (Cancer Nanotechnology, 2023)
Background: In the present era, we are facing different health problems mainly concerning with drug resistance in microorganisms as well as in cancer cells. In addition, we are also facing the problems of controlling oxidative stress and insect originated diseases like dengue, malaria, chikungunya, etc. originated from mosquitoes. In this investigation, we unfurled the potential of Achatina fulica mucus in green synthesis of mucus mediated copper oxide bio-nanocomposites (SM-CuONC) and cobalt oxide bio-nanocomposites (SM-Co3O4NC). Herein we carried out the physico-chemical characterization like UV-Vis spectra, X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Transmission electron microscopy (TEM), Energy Dispersive X-ray Analysis (EDAX) and X-ray photoelectron spectroscopy (XPS) of as synthesized bio-nanocomposites. Both the bio-nanocomposites were tested for their potential as antimicrobial activity using well diffusion assay, anticancer activity by MTT assay, antioxidant activity by phosphomolybdenum assay and mosquito larvicidal activity.Results: The results of this study revealed that, SM-CuONC and SM-Co3O4NC were synthesized successfully using A. fulica mucus. The FESEM and TEM data reveal the formation of nanoparticles with quasi-spherical morphology and average particle size of similar to 18 nm for both nanocomposites. The EDAX peak confirms the presence of elemental copper and cobalt in the analyzed samples. The X-ray diffraction analysis confirmed the crystalline nature of the CuO and Co3O4. The result of anti microbial study exhibited that, SM-CuONC showed maximum antimicrobial activity against Escherichia coli NCIM 2065 and Aspergillus fumigatus NCIM 902 which were noted as 2.36 +/- 0.31 and 2.36 +/- 0.59 cm resp. at 60 mu g/well concentration. The result of anticancer activity for SM-CuONC was exhibited as, 68.66 +/- 3.72, 62.66 +/- 3.61 and 71.00 +/- 2.36 percent kill, while SM-Co3O4NC exhibited 61.00 +/- 3.57, 72.66 +/- 4.50 and 71.66 +/- 4.22 percent kill against Human colon cancer (HCT-15), Cervical cancer (HeLa), and Breast cancer (MDA-MB-231) cell lines, respectively, at 20 mu g/well concentration. Both the nanocomposites also exhibited better antioxidant activity. Total antioxidant activity for SM-CuONC at 50 mu g/ml concentration was found to be highest as 55.33 +/- 3.72 while that of SM-Co(3)O(4)Ns was 52.00 +/- 3.22 mM of ascorbic acid/mu g respectively. Both bio-nanocomposites also exhibited 100% mosquito larvicidal activity at concentration ranging from 40 to 50 mg/l. During cytotoxicity study it is noted that at 5 mu g/well concentration, SM-CuO and SM-Co3O4NCs suspension showed more than 97% viability of normal (L929) cell lines. We also studied phytotoxicity of both bio-nanocomposites on Triticum aestivum. In this study, 100% seed germination was observed when seeds are treated with SM-CuONC and SM-Co3O4NC at 500 mg/l and 250 mg/l concentration respectively.Conclusions: This study concludes that in future as synthesized SM-CuONC and SM-Co3O4NC can be used in pharmaceutical, health care system for betterment and welfare of human life as both bio-nanocomposites exhibits better antimicrobial, anticancer, antioxidant and mosquito larvicidal potential.
Keywords: Achatina fulica mucus; Bio-nanocomposites; Biological activities; Characterization; Toxicity